2021
DOI: 10.3390/ijerph18063116
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Levels of Awareness among European Citizens about the Direct and Indirect Impacts of Plastics on Human Health

Abstract: There is an urgent need to assess European citizens’ perspective regarding their plastic consumption and to evaluate their awareness of the direct and indirect effect of plastics on human health in order to influence current behavior trends. In this study, the evaluation has been cross-related with scientific facts, with the final aim of detecting the most recommendable paths in increasing human awareness, reducing plastic consumption, and consequently impacting human health. A statistical analysis of quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Sanlier [93] showed that young adults' perceptions of food safety risks were "low", resulting in incorrect storing, preparing, thawing, and reheating practices during food preparation. Studies have shown that consumers' attitudes towards use of plastic and littering need changing [28]. We add to those findings that poor utilization habits and ignorance about plastic packaging must also be addressed in line with safety recommendations.…”
Section: Participants' Utilization Practices Of Plastic Food Packagingmentioning
confidence: 77%
See 3 more Smart Citations
“…Sanlier [93] showed that young adults' perceptions of food safety risks were "low", resulting in incorrect storing, preparing, thawing, and reheating practices during food preparation. Studies have shown that consumers' attitudes towards use of plastic and littering need changing [28]. We add to those findings that poor utilization habits and ignorance about plastic packaging must also be addressed in line with safety recommendations.…”
Section: Participants' Utilization Practices Of Plastic Food Packagingmentioning
confidence: 77%
“…Despite the benefits of plastics, they can pose risks to human health and the environment [28] through existing production approaches and consumers' utilization and disposal practices [18]. Although consumers express interest in BPA and its safety [28,29], studies reveal that they are unaware and uninformed about chemical substances in plastic [30] and the effect of these substances on health [28]. Consumers may not know, therefore, that plastic products harmful chemicals migrate from plastic products, and that persistent incorrect utilization practices may adversely affect their health.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although plastic packaging was generally seen not as bad and risky compared to plastic waste and microplastic, its evaluations were negative too. Together with previous research, the current work emphasizes that attitudes related to plastic are negative (Study 1), problem awareness and risk perception are high (e.g., Hartley et al, 2018; Study 2), and many people already try or effectively reduce their plastic consumption (Barbir et al, 2021). Interventions should therefore help consumers to act according to their attitudes by, for example, communicating and providing appropriate alternatives and options for their disposal (e.g., bio-based and fully degradable materials;…”
Section: Discussionmentioning
confidence: 54%